81.3k views
2 votes
Elvate 5-3(X-1) when X=7

User Dmajkic
by
4.5k points

2 Answers

6 votes

To evaluate the expression 5 - 3(x - 1) when x = 7, we need to substitute the value of x, 7, wherever x is present in the expression. Substituting, our expression becomes:

5 - 3(7 - 1)

We now need to do PEMDAS, meaning that we have to simplify the parenthesis first. Doing this, we get:

5 -3(6)

Now wee have to do multiplication.

5 - 18

Now, the final step is to do subtraction.

-13

That means that when x = 7, this expression has a value of -13.

User Shibbir Ahmed
by
5.6k points
5 votes

If x = 7 we just substitute all the x's by seven, so our equation stays like this:

5 - 3(7 - 1)


Now we solve it:

5 - 3(7 - 1) =

5 - 3(6) =

5 - 18 =

-13


Hope it helped,


BioTeacher101


User Cathyann
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.